Effects of 24-epibrassinolide and green light on plastid gene transcription and cytokinin content of barley leaves - Efimova, Marina V; Vankova, Radomira; Kusnetsov, Victor V; Litvinovskaya, Raisa P; Zlobin, Ilya E; Dobrev, Petre; Vedenicheva, Nina P; Savchuk, Alina L; Karnachuk, Raisa A; Kudryakova, Natalia V; Kuznetsov, Vladimir V (Steroids, 2017)
In order to evaluate whether brassinosteroids (BS) and green light regulate the transcription of plastid genes in a cross-talk with cytokinins (CKs), transcription rates of 12 plastid genes (ndhF, rrn23, rpoB, psaA, psaB, rrn16, psbA, psbD, psbK, rbcL, atpB, and trnE/trnY) as well as the accumulation of transcripts of some photoreceptors (PHYA, CRY2, CRY1A, and CRY1B) and signaling (SERK and CAS) genes were followed in detached etiolated barley leaves exposed to darkness, green or white light ±1μm 24-epibrassinolide (EBL). EBL in the dark was shown to up-regulate the transcription of 12 plastid genes, while green light activated 10 genes and the EBL combined with the green light affected the transcription of only two genes (psaB and rpoB). Green light inhibited the expression of photoreceptor genes, except for CRY1A. Under the green light, EBL practically did not affect the expression of CRY1A, CAS and SERK genes, but it reduced the influence of white light on the accumulation of CAS, CRY1A, CRY1B, and SERK gene transcripts. The total content of BS in the dark and under white light remained largely unchanged, while under green light the total content of BRs (brassinolide, castasterone, and 6-deoxocastasterone) and HBRs (28-homobrassinolide, 28-homocastasterone, and 6-deoxo-28-homocastasterone) increased. The EBL-dependent up-regulation of plastome transcription in the dark was accompanied by a significant decrease in CK deactivation by O-glucosylation. However, no significant effect on the content of active CKs was detected. EBL combined with green light moderately increased the contents of trans-zeatin and isopentenyladenine, but had a negative effect on cis-zeatin. The most significant promotive effect of EBL on active CK bases was observed in white light. The data obtained suggest the involvement of CKs in the BS- and light-dependent transcription regulation of plastid genes.
Keywords: Cytokinins; listy rostlin; Plastids; Steroids, Heterocyclic; steroidy heterocyklické; ječmen (rod); Brassinosteroids; genetická transkripce; světlo; brassinosteroidy; cytokininy; plastidy; Hordeum; Light; Plant Leaves; Transcription, Genetic